Working Through Preconception: - Kim Kwok; Antoinette McCallin; Geoff Dickson (Grounded Theory Review: An International Journal)
Much has been written about grounded theory and the processes of theory generation. Less is written about managing the problem of preconception, which has the potential to undermine the openness and emergence that are fundamental to classic grounded theory. The purpose of this paper is to discuss the practical realities of managing preconception, and to draw attention to less well recognised factors that contribute to forcing. The topic interest, tactical innovation in rugby, is introduced. Researcher motivation and the management of preconception are discussed. The example used is the theory of developing, which explains how rugby coaches in New Zealand manage the problem of winning games. The research demonstrates how the novice grounded theory researcher who is prepared to follow the method and trust the process can produce a rigorous grounded theory that makes a meaningful contribution to rugby coaches, players and their administrators.